An Open‐Label, Phase 1 Study to Assess the Effects of Hepatic Impairment on Pomalidomide Pharmacokinetics. Issue 3 (10th May 2018) - Li, Yan; Wang, Xiaomin; Liu, Liangang; Zhang, Chengyue; Gomez, Diana; Reyes, Josephine; Palmisano, Maria; Zhou, Simon
Abstract: Pomalidomide is an immunomodulatory drug and the dosage of 4 mg per day taken orally on days 1‐21 of repeated 28‐day cycles has been approved in the European Union and United States to treat patients with relapsed/refractory multiple myeloma. Because pomalidomide is extensively metabolized prior to excretion, a total of 32 subjects (8 healthy subjects in group 1; 8 subjects with severe hepatic impairment in group 2; 8 subjects with moderate hepatic impairment in group 3; and 8 subjects with mild hepatic impairment in group 4) were enrolled in a multicenter, open‐label, single‐dose study to assess the impact of hepatic impairment on pomalidomide exposure. Following administration of a single oral dose of 4‐mg pomalidomide, the geometric mean ratios of pomalidomide total plasma exposures (AUC) were 171.5%, 157.5%, and 151.2% and the geometric mean ratios of pomalidomide plasma peak exposures (Cmax ) were 75.8%, 94.8%, and 94.2% for subjects with severe, moderate, or mild hepatic impairment, respectively, versus healthy subjects. Pomalidomide administered as a single oral 4‐mg dose was safe and well tolerated by healthy subjects and subjects with severe, moderate, or mild hepatic impairment. Based on the pharmacokinetic results from this study, the pomalidomide prescribing information approved by the US Food and Drug Administration recommends for patients with mild or moderate hepatic impairment (Child‐Pugh classes A or B), a 3‐mg starting daily dose (25% dose reduction) and for patients with severe hepatic impairment (Child‐Pugh class C), a 2‐mg starting daily dose (50% dose reduction).